MANAJEMEN PENDIDIKAN AKHLAK AL-GHOZALI DAN IMPLIKASINYA DI ERA MILENIAL - -, Casrameko (Jurnal Manajemen Pendidikan Islam Al-Idarah, 2024)
Abstract This research discusses the management of Akhlak education according to Al-Ghozali, the life of millennial society, and the implications of Al-Ghozali's Akhlak education in the millennial era. Based on the analysis of Al-Ghozali's thoughts, humans possess three powers: the power of thinking, the power of anger, and the power of desire. When these three powers are well managed to work harmoniously and always refer to reason and Islamic law, they will produce praiseworthy moral actions, namely wisdom (الحكمة), self-purity (العفة), courage (الشجاعة), and justice (العدل), which are the foundations of praiseworthy morals. In this context, Al-Ghozali expresses the theory of the middle path between extreme right and extreme left to achieve noble morals, which need to be applied to the millennial society that is distant from spiritual experiences. Keywords: Management, Al-Ghozali's Akhlak Education, Millennial Era Abstrak Penelitian ini membahas manajemen pendidikan akhlak al-Ghozali, kehidupan masyarakat era milenial, dan implikasi pendidikan akhlak al-Ghozali di era milenial. Berdasarkan analisis terhadap pemikiran al-Ghozali, manusia mempunyai tiga daya yaitu daya berfikir, daya amarah dan daya keingginan dan ketiga daya tersebut di manajemen dengan baik supaya berjalan secara seragam dan senantiasa mengacu pada akal dan syara’, akan menciptakan perbuatan-perbuatan akhlak yang terpuji yaitu kebijaksaan (الحكمة), menjaga kesucian diri (العفة), keberanian (الشجاعة), keadilan (العدل), yang menjadi pokok keutaaman akhlak terpuji, dalam hal ini al-Ghozali mengungkapkan teori jalan tengah antar ekstrem kanan dan ekstrem kiri untuk memperoleh akhlak yang mulia yang perlu diterapkan kepada masyarakat milenial yang jauh dari pengalaman spiritual. Kata Kunci: Manajemen, Pendidikan Akhlak al-Ghozali, Era Milenial